Analyzing the impact of non-participation in the FIFA World Cup Qatar 2022 on LaLiga players' physical performance - Reverte-Pagola, Gonzalo; Pecci, Javier; del Ojo-López, Juan José; del Campo, Roberto López; Resta, Ricardo; Feria-Madueño, Adrián (Frontiers in Sports and Active Living, 2024)
Background Monitoring external load demands in soccer is crucial for optimizing performance and reducing injury risk. However, events like the FIFA World Cup Qatar 2022 and unexpected interruptions can disrupt load management strategies. Understanding the impact of such events on player performance is essential for effective training and recovery strategies. Objective This study retrospectively assessed the impact of the FIFA World Cup Qatar 2022 on the physical performance of LaLiga elite soccer players who were not part of the tournament. The aim was to analyze various external load parameters and determine the direction of their changes post-tournament. Methods Data from 239 LaLiga players who were not selected for the World Cup were analyzed. External load parameters from 8 matches before and after the tournament were compared. Statistical analyses, including repeated measures ANOVA, were conducted to evaluate changes in performance metrics. Results Minutes played and total distance covered showed no significant changes post-tournament. However, maximal speed decreased significantly (p < 0.001; η2p = 0.117). High-speed running parameters improved significantly (p < 0.05), except for HSRRelCount (p = 0.074; η2p = 0.013). Sprint-related variables demonstrated significant enhancements, except for SprintAbsAvgDuration, SprintMaxAvgDuration, and Sprints >85% Vel Max. Acceleration metrics showed significant improvements in Accel_HighIntensityAccAbsCount (p = 0.024; η2p = 0.021), while Accel_Accelerations showed no significant changes. Deceleration metrics remained unchanged, but Accel_HighIntensityDecAbsCount and Accel_HighIntensityDecAbsDistance increased significantly post-tournament (p = 0.002; η2p = 0.040, p = 0.001; η2p = 0.044, respectively). Conclusion Non-participant LaLiga players demonstrated enhanced performance in most external load metrics after the FIFA World Cup Qatar 2022. These findings highlight the importance of effective load management during periods of competition interruption and suggest strategies to optimize performance and reduce injury risk. Further research should consider holistic performance metrics and internal load parameters to provide comprehensive insights into player response to mid-season tournaments.